Structural determination of the polysaccharide isolated from biofilms produced by a clinical strain of Klebsiella pneumoniae. (22nd July 2016) - Cescutti, Paola; De Benedetto, Gianluigi; Rizzo, Roberto
Highlights: Klebsiella pneumoniae strain Ts113 (KpTs113) was isolated from a urinary tract infection. KpTs113 was grown on cellulose membranes to form biofilms. KpTs113 in liquid medium produced flocs. Biofilms on cellulose membranes and flocs contained the same polysaccharide. The polysaccharide produced by KpTs113 is identical to that of Klebsiella K24. Graphical abstract: Abstract: Klebsiella pneumoniae are Gram negative opportunistic pathogens producing capsular (K) polysaccharides. Seventy-seven different K antigens have been described and they are the basis for K serotyping. Capsular polysaccharides are important virulence factors and have a relevant role for the structure of biofilm communities. Nevertheless, little information is available on the polysaccharides produced in biofilm matrices by Klebsiella spp. In the present study, a clinical isolate of Klebsiella pneumoniae was grown both on cellulose membranes deposited on agar plates, where it formed an adherent biofilm, and in liquid medium, where it formed floating biofilms (flocs). Extraction and purification of the polysaccharide fraction showed that only one main carbohydrate polymer was present in both adherent biofilms and flocs. Composition and linkage analysis, Smith degradation followed by ESI-MS, 1D and 2D NMR spectroscopy revealed that the polysaccharide belong to the type K24 and has the following structure: